2015
DOI: 10.1007/s00227-015-2754-1
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle and early development of the thecosomatous pteropod Limacina retroversa in the Gulf of Maine, including the effect of elevated CO2 levels

Abstract: Thecosome pteropods are pelagic molluscs with aragonitic shells. They are considered to be especially vulnerable among plankton to ocean acidification (OA), but to recognize changes due to anthropogenic forcing a baseline understanding of their life history is needed. In the present study, adult Limacina retroversa were collected on five cruises from multiple sites in the Gulf of Maine (between 42° 22.1'-42° 0.0' N and 69° 42.6'-70° 15.4' W; water depths of ca. 45-260 m) from October 2013−November 2014. They w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
73
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(76 citation statements)
references
References 55 publications
3
73
0
Order By: Relevance
“…were corroborated in the GoM by observations of egg laying in the lab after seasonal sampling479 Thabet et al, 2015), which documented egg production in all seasons but noted that it was 480 particularly high in April and October.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…were corroborated in the GoM by observations of egg laying in the lab after seasonal sampling479 Thabet et al, 2015), which documented egg production in all seasons but noted that it was 480 particularly high in April and October.…”
mentioning
confidence: 73%
“…Understanding these cycles is important because they can reveal periods that could 123 serve as population "bottlenecks" under future anthropogenically acidified conditions. One 124 potential bottleneck is the life stage when initial biomineralization occurs, as it has been 125 demonstrated to be one of the most sensitive for both pteropods and other molluscan groups 126 (Thabet et al, 2015;Waldbusser et al, 2013;Waldbusser et al, 2015;White et al, 2013). It 127 remains mostly unclear when, and due to what physical factors, L. retroversa spawns in the 128 North Atlantic.…”
mentioning
confidence: 99%
“…Larval growth impairment showed a significant difference in the magnitude of response in comparison with adults and was one of the most sensitive to ar . Of those studies measuring ar growth impacts, data could only be obtained for the study by Manno et al (2012) but not from Thabet et al (2015) and Comeau et al (2010b) because LOE could not be extracted, or the uncertainty was too great, yet both studies demonstrated a significant decrease in larval growth and developmental delay. The derived LOE based on Manno et al (2012) was ar = 1.15 for 7 days.…”
Section: Growth Reductionmentioning
confidence: 99%
“…Examinations of seasonal changes in size distributions and gonad development have suggested L. retroversa spawning peaks in the GoME in May, but with active reproduction continuing into the fall [Hsiao, 1939]. A recent laboratory study of L. retroversa reproductive and developmental biology also found that this species is capable of spawning multiple times per year, and suggest that, in this region, individuals likely live 6 months [Thabet et al, 2015]. Abundances of small individuals were very high in May 2013 and April-June 2015, indicative of a strong springtime spawning event, presumably associated with the spring bloom.…”
Section: Pteropod Abundancementioning
confidence: 99%
“…Alternatively, it may represent an indirect association between pteropod abundance and Journal of Geophysical Research: Oceans 10.1002/2016JC012373 X-Ar mediated by synchrony between the pteropod life cycle and senescence after reproductive events with times of high productivity (i.e., spring and fall blooms) at which time enhanced DIC serves to decrease X-Ar. Related to this notion, it is possible that the life cycle of L. retroversa in the region is optimized such that large reproductive adults are most abundant during periods when their larvae have a better chance of passing the initial calcification bottleneck [Thabet et al, 2015;Waldbusser et al, 2013Waldbusser et al, , 2015, and this causes successful cohorts to appear in large numbers during periods when X-Ar is high (as well as food abundant). If so, it will become useful to consider how the predicted changes in saturation state might influence their future spawning success.…”
Section: Pteropod Abundancementioning
confidence: 99%